CUSTOMER SATISFACTION MODERATES EXPERIENTIAL MARKETING ON GRAB-BIKE USER LOYALTY - Muh Hasan; Eko Narto (Dynamic Management Journal, 2026)
Intense competition in the online transportation industry requires companies to create unique customer experiences, particularly through experiential marketing. GrabBike, as a leading service provider in Tangerang City, faces significant challenges in maintaining customer loyalty. This study aims to examine the effect of experiential marketing on customer loyalty with customer satisfaction as a moderating variable among GrabBike users. A quantitative approach with a descriptive-associative design was employed. The sample comprised 100 respondents selected through purposive sampling, and the data were analyzed using SmartPLS 4.0. The results indicate that experiential marketing significantly affects customer satisfaction but does not directly affect customer loyalty. However, customer satisfaction significantly affects loyalty, and experiential marketing does so through customer satisfaction as a moderating variable. This study contributes theoretically by clarifying the role of customer satisfaction as a moderator rather than a mediator—in the experiential marketing-loyalty relationship, an area rarely explored in the online transportation context. The novelty lies in revealing that satisfaction strengthens the indirect effect of experiential marketing on loyalty, offering a nuanced understanding of their interrelationship. Practically, these findings provide strategic insights for GrabBike management to prioritize satisfaction-driven experiential marketing. Methodologically, this study demonstrates the application of SmartPLS to test moderating effects in a non-linear service setting, specifically among GrabBike users in Tangerang, an emerging urban market.